SIKAP SOSIAL SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN KELAS IX DI SMP NEGERI 1 KOTO GASIB - Rilnaldi, Puja Dwi; Vai, Aref; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the Social Attitudes of Students in Learning Physical Education, Sport and Health Class IX at SMP Negeri 1 Koto Gasib. This research is a quantitative descriptive study with a population of 115 students in grade IX at SMP Negeri 1 Koto Gasib.sampling technique in this study was random sampling because the sampling of members of the population was carried out randomly without regard to the existing strata in the population as much as 25%-30% of the population, namely 32 students. Data was collected using observation, questionnaires and documentation. Test the validity of the instrument using the product moment with a significant level of 5% and the reliability test of the instrument using the Cronbach alpha through the IBM SPSS Statistics 22 stating that all items are valid stated by R arithmetic > from R table (0.349) and reliability test with Cronbach'sAlpha 0.969. The results showed that (1) Honest with a percentage of 8.55%. (2) Discipline 8.44%. (3) Liability 12.80%. (4) Tolerance 17.03%. (5) Gotong Royong 12.47%. (6) Polite/ Polite 17.78%. (7) Confidence 7.95%. Thus the Social Attitude of Students in Learning Physical Education, Sport and Health Class IX at SMP Negeri 1 Koto Gasib is said to be very good with an Interpretation Criteria score of 85.02%.Key Words: Social Attitude, Physical Education, Sports and Health